THE PHENOMENON OF SLANG LANGUAGE ON FACEBOOK AND TWITTER - Istifatun Zaka (Universitas PGRI Yogyakarta, 2015)
This paper describes about the phenomenon of slang language on social network, namelyfacebook and twitter. Slang in this paper belongs to sociolinguistics study, especially sociolect. This isa descriptive qualitative method, which consists of three phase: data collection, data analysis, andpresentation of the result of data analysis. The data were collected by observing the netters utterance.Data were analysed through two phases. First, analyzing the meaning of the slang. Second, wasanalysing the categories of the slang.There are four point findings in this study. Firstly, the various forms of slang expression unitsare words and phrases. Secondly, the variety of linguistic processes forming units slang expression areby adding sound, erasing sound, changing vocal, replacing consonant, shifting sound, returning sound,repeating, and changing spell. Thirdly, the source languages of various slang reference units are fromnational language, regional languages, and foreign languages. Fourthly, the communicative functionsof various units of slang expressions are informative function, directive function, expressive function,komisif function, phatic function, and poetic function. Finally, from the finding of those four points inthis study, we know that slang language on facebook and twitter has its own uniqueness compared toother types of language.